Kauno universiteto fakultetų ir jų padalinių bibliotekos - Lietuvninkaitė, Nijolė (Knygotyra, 2024)
In this article, the work of the libraries of Kaunas University faculties up to 1940 is analyzed. Their principal task was to provide readers with scientific and educational literature. The Technical Faculty, Theological-Philosophical Faculty, Faculty of Law, and Faculty of Humanities possessed the largest libraries. Other faculties organized libraries and collections of printed materials (no more than 1000 copies) in departments, laboratories, and for studies and seminars. The acquisition funds were assigned by the State Budget. Acquisition sources included bookstores, international library loans, and gifts. The libraries of the faculties operated independently until 1940. They assisted the Central Library of Kaunas University in providing its readers with literature necessary for studies. The libraries also took part in the pedagogical and scientific work of Kaunas University.